Odpowiedź :
7x²-21x-14-3x²+18x-3
7(-0.2)²-21(-0.2)-14-3(-0.2)²+18(-0.2)-3
0.28+4.2-14-0.12-3.6-3
=-16.24
b)
x(3xy - y) - y(x² - xy + x)
3x²y-xy-x²y+xy²-xy
2x²y+xy²-xy-x
2(-1)²0.2+(-1)0.2²-(-1)0.2-(-1)0.2
0.4-0.04+0.2+0.2
=0,76
7(-0.2)²-21(-0.2)-14-3(-0.2)²+18(-0.2)-3
0.28+4.2-14-0.12-3.6-3
=-16.24
b)
x(3xy - y) - y(x² - xy + x)
3x²y-xy-x²y+xy²-xy
2x²y+xy²-xy-x
2(-1)²0.2+(-1)0.2²-(-1)0.2-(-1)0.2
0.4-0.04+0.2+0.2
=0,76
A) 7(0.04+0.6-2)-3(0.04+1.2+1)=7*(-1.36)-3*2.24=-9.52-6.72=-16.24
B) -1(-3*0.2-0.2)-0.2(1+0.2-1)=0.8-0.04=0.76
B) -1(-3*0.2-0.2)-0.2(1+0.2-1)=0.8-0.04=0.76